How Does Workplace Ostracism Lead to Service Sabotage Behavior in Nurses: A Conservation of Resources Perspective - Sarwar, Ambreen; Abdullah, Muhammad Ibrahim; Hafeez, Hira; Chughtai, Muhammad Ahsan (Frontiers in Psychology, 2020)
This paper aims to investigate how workplace ostracism acts as a motive behind customer service sabotage. We examine the role of stress as a meditating variable along with the moderation of perceived organizational support (POS) on the said association by using conservation of resources and equity theory. 217 nurses from hospitals of southern Punjab region in Pakistan participated in the study. Data was collected through survey and structured questionnaires. SPSS and AMOS were used to analyze data with latest techniques of bootstrapping and process macros. The results showed that stress mediated between the association of workplace ostracism and service sabotage behavior. Perceived organizational support was confirmed as a moderator between this relationship. POS buffered the harmful effects of ostracism and stress on customer service, as POS demonstrates to personnel that they are cherished and respected by the organization which lessens the strength of perceived stress due to workplace ostracism. Organizational leadership should take advantage from stress-alleviating effect of POS, which is important in producing adequate levels of work-performance.